Sweet's Syndrome: a case report - BMM Kayastha; L Lama; P Shrestha; R Shrestha; A Karki (Nepal Journal of Dermatology, Venereology & Leprology)
Sweet's syndrome is a disorder characterized by fever and painful skin lesions. The condition starts suddenly with the appearance of red, slightly raised tender plaques, usually on the back, arms, face or neck. Women are most at risk of Sweet's syndrome, predominantly between 30-50 years of age who have recently had an upper respiratory tract infection. Here we present a 70 years old lady who came with fever and tender erythematous plaques on trunk and limbs. On investigation, leucocytosis with raised ESR was found and the skin biopsy was consistent with Sweet's syndrome. There was dramatic improvement with systemic corticosteroid.